Nilai - Nilai Keluarga Sebagai Basis Usaha Batik Studi Kasus Keluarga Luas Sedewo di Patangpuluhan, Yogyakarta - , ARIEF ERLANGGA P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yogyakarta belongs to the city of Batik in Indonesia, instead on Pekalongan and Solo, in which certainly plays a very important rule to preserve Batik. The existence of batik is inseperable from entrepreneurs or artistsâ role engaged in it and familly business plays an important role as well. This research uses descriptive qualitative method which is expected to be able to describe familya life an activitive in the batik business familly. In this research, the data were collected from participatory observation and in-depth interviews and informants. They are the business owners employee, and relatives who assist the batik business. Batik business in this family has been running for long time, so there are lot of the family values that can make batik business survive until day. Family certainly cannot be separated from where they come from or live, and Javanese culture which they hope steadfast over the years, the family values that makes the writer interested. This study concludes that the batik business in strongly influenced by family values. The values in this family such as cooperation and get along each other, respect, shynes, and compassion, play an important rule. With these values, the batik family business passes down to the next generation, so batik industry can survive until today.